2012
DOI: 10.1530/eje-12-0472
|View full text |Cite
|
Sign up to set email alerts
|

Vasoregulatory peptides pro-endothelin-1 and pro-adrenomedullin are associated with metabolic syndrome in the population-based KORA F4 study

Abstract: Background: Metabolic alterations and endothelial dysfunction are interrelated processes in type 2 diabetes (T2D) and metabolic syndrome (MetS) that often develop in parallel. We assessed the association of vasoactive precursor peptides (VPPs) with MetS and T2D. Design and methods: Plasma levels of C-terminal pro-endothelin-1 (CT-proET-1) and midregional proadrenomedullin (MR-proADM) were measured by novel sensitive assays in 1590 participants of the population-based KORA F4 study. The association of the VPPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
(51 reference statements)
5
26
1
Order By: Relevance
“…The applied analyses methods to determine glutamate pyruvate transaminase, glutamic oxaloacetic transaminase, gamma-glutamyl transpeptidase, C-reactive protein (Ruckert et al 2011), cystatin C (Goek et al 2012), and creatinine (Seissler et al 2012), concentrations have been described earlier. White blood cell count was determined from fresh venous EDTA blood using impedance measurements (Coulter ® LH 780, Beckman Coulter Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…The applied analyses methods to determine glutamate pyruvate transaminase, glutamic oxaloacetic transaminase, gamma-glutamyl transpeptidase, C-reactive protein (Ruckert et al 2011), cystatin C (Goek et al 2012), and creatinine (Seissler et al 2012), concentrations have been described earlier. White blood cell count was determined from fresh venous EDTA blood using impedance measurements (Coulter ® LH 780, Beckman Coulter Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…Also, studies found association of ProADM with metabolic syndrome and its components, i.e. type 2 diabetes [39, 40]. …”
Section: Introductionmentioning
confidence: 99%
“…Significant positive correlation between ADRB2 and ADM expressions and between ROCK1 and HSPB1 during a post-exercise recovery process seems to confirm the protective effect of the adrenergic system on the cardiovascular function (Yahiaoui et al, 2008). The ADM gene encodes a vasoregulatory protein which controls vascular tone and enhances myocardial contractility (Seissler, 2012). The tendency of a lower ADM expression during exercise and higher during 15 minutes of recovery, respectively might reflect low vascular resistance during endurance training.…”
Section: Discussionmentioning
confidence: 99%